AGREEMENT BETWEEN INSTRUMENTS FOR ASSESSMENT OF BODY BALANCE IN ACTIVE ELDERLY INDIVIDUALS - Marcelo de Maio Nascimento; Nayara Jéssica dos Santos Maia; Lucas da Silva Ramos; Hans-Joachim Appell Coriolano (Journal of Physical Education)
ABSTRACT The aim of this study was to analyze the correlation between the instruments used to assess body balance and prediction of the risk of falls of active seniors. Cross-sectional, observational study involving 41 women (69.24 ± 5.24 years) practitioners of physical exercises, in Petrolina-PE. The instruments used were the Berg Balance Scale (BBS), the Dynamic Gait Index (DGI), the "Timed Up and Go" simple (TUG), the "Timed Up and Go" motor (TUGm), the "Timed up and Go "cognitive (TUGc) and Body Balance Test (CET). Significant correlation was observed between TEC-DGI (r = 0.469; p = 0.032), BSE-DGI (r = 0.513; p = 0.021), a significant negative correlation between DGI-TUG (r = -0.454; ˂0,017), DGI -TUGm (r = -0.516; p˂0,006), DGI-TUGc (r = -0.547; ˂0,003), MMSE-TUG (r = -, 470; p = 0.055), MMSE-TUGm (r = - 470; p = 0.057) and a significant and moderate correlation between TUG-TUGm (r = 0.701; p = 0.000), TUG-TUGc (r = 0.713; p = 0.000) and TUGm-TUGc (r = 0.761; p = 0.000). It is concluded that the instruments are complementary. It is recommended their joint application to the evaluation of the body balance and to predict the risk of falls in elderly active.